2020
DOI: 10.1093/cid/ciaa329
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between COVID-19 Mortality and the Renin-Angiotensin System? A Call for Epidemiologic Investigations

Abstract: Mortality from coronavirus disease 2019 (COVID-19) is strongly associated with cardiovascular disease, diabetes, and hypertension. These disorders share underlying pathophysiology related to the renin-angiotensin system (RAS) that may be clinically insightful. In particular, activity of the angiotensin-converting enzyme 2 (ACE2) is dysregulated in cardiovascular disease, and this enzyme is used by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to initiate the infection. Cardiovascular disease and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
248
0
17

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(268 citation statements)
references
References 29 publications
3
248
0
17
Order By: Relevance
“…The favorable effects of ACE inhibitors and ARBs on the control of the progression of CVDs in general and in particular of hypertensive patients have been confirmed for many years and for this reason RAS inhibitors represent central agents for the management of cardiovascular conditions that cannot be easily substituted [10]. C. In hypertensive patients with COVID-19 or at risk of COVID-19 infection, ACE inhibitors and ARBs treatment should be maintained according to the recommendations contained in the 2018 ESC/ESH guidelines [10]. D. Similarly, in all patients currently on therapy with ACE inhibitors, ARBs and in the case of patients with heart failure, also the ARNIs, these drugs must not be suspended.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The favorable effects of ACE inhibitors and ARBs on the control of the progression of CVDs in general and in particular of hypertensive patients have been confirmed for many years and for this reason RAS inhibitors represent central agents for the management of cardiovascular conditions that cannot be easily substituted [10]. C. In hypertensive patients with COVID-19 or at risk of COVID-19 infection, ACE inhibitors and ARBs treatment should be maintained according to the recommendations contained in the 2018 ESC/ESH guidelines [10]. D. Similarly, in all patients currently on therapy with ACE inhibitors, ARBs and in the case of patients with heart failure, also the ARNIs, these drugs must not be suspended.…”
Section: Recommendationsmentioning
confidence: 99%
“…Indeed, the observed prevalence of male and elderly patients, observed especially in the Italian COVID-19 population, is a confounding factor that needs to be corrected for before any conclusive association is drawn. This concern has been expressed by many [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of ACE2 was reported to enhance viral entry and replication intracellularly [4]. COVID-19, also called SARS-CoV-2, may also use ACE2 as a receptor to initiate infection, leading to severe complications from the heart (acute coronary syndrome (ACS) and fulminant myocarditis), lungs (pneumonia and acute respiratory distress syndrome (ARDS)) and GI tract (diarrhoea syndrome) [5].…”
mentioning
confidence: 99%
“…However, before implementing such strategies, we should consider several issues. Firstly, as the COVID-19 infection progresses, ACE2 is downregulated, thus potentially generating an inflammatory response leading to impaired cardiac contractility and acute lung injury [5,7,12]. Therefore, reduced ACE2 expression is linked to worse outcomes.…”
mentioning
confidence: 99%
“…When infected with SARS-CoV-2, the virus predominantly targeted ACE2 in human alveolar type 2cells, resulting in pulmonary symptoms [27]. It has been reported that ACE2 was associated with comorbidities, symptoms and complications in COVID-19 patients, such as hypertension, diabetes, cardiovascular disease and gastrointestinal abnormalities [28]. However, the mechanism still remains unclear.…”
Section: Discussionmentioning
confidence: 99%